Review of Outpatient Department Spencer Eye Hospital (A Study of 1900 Patients) - M. Rais, Uzma Fasih, Arshad Shaikh, Atiya Rahman, M. S. Fehmi (Pakistan Journal of Ophthalmology, 2018)
Purpose: To determine the pattern of different diseases among the patients attending the OPD. Material and Methods: The study was carried out at outpatient department Spencer Eye Hospital from March 2011 to July 2011 and included 1,900 patients. Patients were selected from outpatient department Spencer Eye Hospital through non probability consecutive sampling technique. Relevant history was taken. They were examined thoroughly including detailed slit lamp examination, direct and indirect fundoscopy and refraction. Diagnosis was established and data of the patient was recorded and later on compiled. Results: Nineteen hundred patients were included in the study, 900 (47.3%) were male and 1000 (52.7%) were female. Most commonly presenting age group among male patients was 60 – 69 years, while most common age group among female patients was 40 -49 years. We observed that the main bulk of the OPD consisted of patients who presented with infectious conjunctivitis (mostly trachoma) (24%) and with cataract (23.1%), followed by those who presented with refractive error (17.4%). Presentation of pterygium and corneal ulcer was 11.0% and 3.02% respectively. Cases of glaucoma and strabismus, were 2.8% and 1.28% respectively. Few patients with vitamin A deficiency and albinism also reported. Conclusion: Infectious diseases and cataract are more prevalent in this area as compared to other ocular disorders especially of posterior segment. So the available funds should be directed in these lines.